Integrating advanced computer-aided design, manufacturing, and numerical control [ principles and implementations - Xu, Xun , 1959- (Hershey, PA. : Information Science Reference, 2009)
"This book presents basic principles of geometric modelling while featuring contemporary industrial case studies"--Provided by publisher
"Premier reference source"--Cover
Description based on print version record
Includes bibliographical references and index
Keywords: CAD/CAM systems; Geometrical models -- Data processing; Industrial design -- Data processing